Effect of L-arginine on the optical properties, crystalline perfection and laser damage threshold of KDP crystals - Kostenyukova, E.I.; Bezkrovnaya, O.N.; Tkachenko, V.F.; Kolybaeva, M.I.; Sofronov, D.S.; Dolzhenkova, E.F.; Lopin, A.V.; Pritula, I.M. (Functional Materials, 2015)
Potassium dihydrogen phosphate (KDP) single crystals doped with L-arginine amino acid were grown from aqueous solutions onto a point seed using the temperature reduction method. The incorporation of L-arg molecules into the crystal was verified by the methods of UV-vis-IR and FTIR spectroscopy. It was shown that the entering of L-arg into the matrix was accompanied with the increase of the volume of KDP:L-arg elementary cell by ~ 2·10⁻²Å³ with respect to the one of the pure crystal. There was analyzed the influence of L-arg molecules on the value of laser damage threshold for different growth sectors of KDP crystal. The laser damage threshold of KDP:L-arg crystal was found to rise for the growth sector {101} and to diminish for the growth sector {100} with respect to the corresponding parameter of the pure crystal.